Climate change and biogeographic connectivity across the Brazilian cerrado. (11th November 2019) - De Oliveira, Paulo E.; Raczka, Marco; McMichael, Crystal N. H.; Pinaya, Jorge L. D.; Bush, Mark B.
Abstract: Aim: To investigate cerrado responses to glacial–interglacial climate change and the potential for connective rain forest corridors between the Atlantic Coastal Forest and Amazonian rain forest. Location: The crater lake of Serra Negra (18 °S, 46 °W) in Minas Gerais, Brazil. Taxon: 117 fossil pollen types, 22 non‐pollen palynomorphs were documented. Methods: We recovered 7.82 m of sediment from the lake, and analysed fossil pollen at 62 depth intervals throughout the core. We derived a chronology based on radiocarbon dating with simple rate extrapolation to the base of the core. Results: The c. 90, 000‐year fossil record showed a trend towards cooler climates at the Last Glacial Maximum (LGM), but interstadial warming coupled with reduced evaporative stress allowed the expansion of woodlands under cool, moist conditions. Cool‐adapted trees were most abundant between c. 67, 000 and 48, 000 years ago. A cool cerrado‐like environment marked full glacial conditions between c. 48, 000 and 34, 000 years ago. The peak of the LGM between c. 34, 000 and 17, 000 years ago is inferred to have been dry as no sediment accumulated in the system. Main conclusions: Expanded ranges of cold‐tolerant forest taxa led to establishment of a series of assemblages without modern analogue. A system characteristic of modern cerrado was rare in the history of this site. Multiple forest expansions were observed, each differing in composition. The periods of forest abundance at Serra Negra were not temporally aligned with forest expansion in the Atlantic Coastal Forest, and did not provide a continuous corridor of similar forest that connected the cerrado to the Atlantic Coastal Forest.